Association of Non-alcoholic Fatty Liver Disease With Salt Intake and Dietary Diversity in Chinese Medical Examination Adults Aged 18–59 Years: A Cross-Sectional Study - Luo, Xiaofei; Li, Ying; Zhou, Yi; Zhang, Chun; Li, Lijun; Luo, Yating; Wang, Jiangang; Duan, Yinglong; Xie, Jianfei (Frontiers in Nutrition, 2022)
Objectives: Given the significance of dietary factors in the development of non-alcoholic fatty liver disease (NAFLD). We conducted a cross-sectional study to investigate the association of NAFLD with salt intake and dietary diversity in a medical examination population aged 18-59 years. Methods: Data from two Chinese health management centers were utilized between January 2017 and December 2019. The general information, laboratory tests, lifestyle habits, and diet of the participants were all evaluated. Based on alcohol consumption and abdominal ultrasound results, a total of 23,867 participants were divided into the NAFLD (n = 7753) and control (n = 16,114) groups. Salt intake and dietary diversity were calculated separately for study participants using the spot urine method and dietary diversity scores (DDS). The multilevel logistic model and subgroup analysis were used to analyze the relationship between salt intake, dietary diversity, and NAFLD. Results: We found that the prevalence of NAFLD was 32.48%. Salt intake was associated with increased NAFLD (Q2 vs. Q1: OR = 1.201, 95% CI 1.094-1.317, P < 0.001; Q3 vs. Q1: OR = 1.442, 95% CI 1.316-1.580, P < 0.001; Q4 vs. Q1: OR = 1.604, 95% CI 1.465-1.757, P < 0.001), whereas sufficient dietary diversity was a protective factor for NAFLD (Sufficient DDS vs. Insufficient DDS: OR: 0.706, 95% CI 0.517-0.965, P < 0.05). The effects of salt intake and dietary diversity on NAFLD were equally stable in the subgroup analysis. Conclusions: We can conclude that NAFLD is highly prevalent in medical examination adults aged 18-59 years in China. Furthermore, the risk of salt intake for NAFLD and the protective effect of dietary diversity on NAFLD should be taken into account in the management of NAFLD.